PENGARUH KUALITAS PELAYANAN, TRUST DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN NASABAH BANK BCA DI KABUPATEN JOMBANG - Rosita Ainurrochimah; Wisnu Mahendri (Bussman Journal : Indonesian Journal of Business and Management, 2023)
In this research sample, respondents were taken from BCA bank customers in Jombang Regency. The number of samples used in this research was adjusted to the analysis method used, namely the Structural Equation Model (SEM). In the SEM method, the number of samples required is at least 5 times the number of indicator variables. The number of indicators in this research is 16 indicators, so a minimum of 16 X 5 = 80 samples are needed. The results of the research concluded that there was a significant effect on the service quality variable on bank customer satisfaction, and there was a significant effect on the trust variable on customer satisfaction, but the customer experience variable produced a positive but not significant effect on BCA bank customer satisfaction. Then this research resulted that the three independent variables, namely service quality, trust and customer experience, had a joint or simultaneous effect on customer satisfaction, which shows that overall customers were satisfied with the services provided by the company and were in accordance with their needs or whatever. what customers want. However, it is recommended that companies continue to increase customer satisfaction in order to make the customer experience even better and must continue to maintain and improve the quality of service and customer trust so that the level of satisfaction becomes better